Substantial decrease in SARS-CoV-2 RNA after fixation of cadavers intended for anatomical dissection - Vymazalová, Kateřina; Šerý, Omar; Králík, Petr; Dziedzinská, Radka; Musilová, Zuzana; Frišhons, Jan; Vojtíšek, Tomáš; Joukal, Marek (Anatomical science international, 2023)
With the onset of the COVID-19 pandemic, a problem arose with classic body donation programmes for obtaining cadavers for anatomical dissections, science and research. The question has emerged whether bodies of individuals who died of COVID-19 or were infected by SARS-CoV-2 could be admitted to Departments of Anatomy. To determine the risk of SARS-CoV-2 transmission to employees or students, the presence and stability of SARS-CoV-2 RNA in cadavers after fixation agents' application and subsequent post-fixation baths over time were examined. The presence of viral RNA in swabs from selected tissues was assessed by the standardized routine RNA isolation protocol and subsequent real-time PCR analysis. To support the results obtained from the tissue swabs, samples of RNA were exposed in vitro to short and long-term exposure to the components of the injection and fixation solutions used for the bodies' conservation. Substantial removal of SARS-CoV-2 RNA was observed in post-mortem tissue following perfusion with 3.5% phenol, 2.2% formaldehyde, 11.8% glycerol and 55% ethanol, and subsequent post-fixation in an ethanol bath. In vitro experiments showed significant effects of formaldehyde on SARS-CoV-2 RNA, while phenol and ethanol showed only negligible effects. We conclude that cadavers subjected to fixation protocols as described here should not pose a considerable risk of SARS-CoV-2 infection while being handled by students and staff and are, therefore, suitable for routine anatomical dissections and teaching.
Keywords: ethanol; lidé; RNA virová; Pandemics; Coronavirus; Formaldehyde; Humans; SARS-CoV-2; pandemie; mrtvola; Ethanol; RNA, Viral; COVID-19; Phenols; Polymerase chain reaction; Infections; formaldehyd; Dissection; Embalming; fenoly; Cadaver